Therapeutic Effect of Conductive Education Rehabilitation Training on Children with Cerebral Palsy - Yifang CAI; Haiyan HUANG; Xiaofeng QIU (康复学报)
Objective:To observe the effects of conductive education rehabilitation training on motor function and daily life activities of children with cerebral palsy (CP).Methods:93 CP children were assigned to observation group (n=63) and control group (n=30) according to whether to persist in conductive education. Both groups received comprehensive rehabilitation treatment constantly. The observation group was added with conductive education rehabilitation training for more than three months, and the control group received conductive education rehabilitation training for less than three months. Gross motor function measure 88 (GMFM-88) and activity of daily living (ADL) scale were used to evaluate the effectiveness of rehabilitation.Results:GMFM-88 score and ADL score in both groups were increased significantly after training (P<0.01, P<0.05), GMFM-88 score and ADL score in observation group were significantly higher than those in control group after training (P<0.01). The difference-values of GMFM-88 score and ADL score of children with younger age (3~4 years old) were significantly higher than those of older age children (4~7.5 years old) in observation group (P<0.01).Conclusion:Conductive education combined with comprehensive rehabilitation therapy could improve motor function and ADL of CP children, and the curative effect is better than that of single comprehensive rehabilitation therapy. The curative effect of conductive education combined with comprehensive rehabilitation therapy for younger age children is superior to the older age children.